A comparative study of robust control methods applied to vehicle anti-roll system by active sway bar. - Paes, Joed Henrique (2018)
Anti-roll bars aim to increase the vehicle\'s safety during curved trajectories. By reducing the roll angle, the bars minimize the risk of overturning during cornering in function of the increasing lateral acceleration, and also, as a consequence, improves the steering comfort. This work presents studies of vehicle\'s lateral dynamics in three dierent approaches: a vehicle without anti-roll system, a vehicle with passive roll bar and a vehicle with an active anti-roll bar. The active anti-roll bar is controlled by a torque-generating motor and comparisons between two robust controllers is presented. The bars are modeled by FEM (Finite Element Method) and controllers LQG/LTR (Linear Quadratic Gaussian/ Loop Transfer Recovery) and H? Loop-Shaping are designed to the active system in order to evaluated the best option. In addition, the vehicle\'s lateral dynamic is hybridized to the exible bar model in order to obtain an unique system. It reviews the vehicle\'s roll dynamic and describes in detail the FEM applied to dynamic modeling of exible structures. The influence of the active anti-roll system and the different controllers are illustrated through numerical simulation and a comparison between the passive system and the system without bar is performed.